Estimation of Some Immunological Parameters Levels in Giardiasis Patients in Al- Najaf Province - Jameel Jerri Yousif (Journal of Global Pharma Technology, 2016)
The current study was conducted during the period from August 2017 to April 2018 in the Department of Biology - Faculty of Education for Girls - University of Kufa to measure the level of some cytokines and immunoglobulins in patients with Giardia lamblia parasite in Al- Najaf Province. A total of 923 stool samples from patients, with diarrhea ranging in age from 1 to 60 years were examined with a direct smear and sedimentation methods. The results of the immunological examination were shown using the enzyme linked immunosorbent assay (ELISA) and single radial immunodiffusion (SRID) Plate. IgA, IgE, IgG and IgM concentrations were increased in patients with Giardiasis as 276 ± 32.3 mg / dl, 260 ± 39.3 IU / ml, 576 ± 42.4 mg / dL and 73 ± 17.8 mg / dL , respectively, compared with the control group of 65 ± 22.7 mg / dl, 175 ± 23.3 IU / ml, 365 ± 27.3 mg / dl and 47 ± 14.4 mg / dl, respectively, with a statistically significant difference P <0.05.As well as an increase in concentrations of IFN-γ , IL-4 and TNF-α (284 ± 21.4, 395 ± 27.1 and 443 ± 29.2) pg / mL respectively compared to control group (131 ± 18.7, 345 ± 22.6 and 191 ± 26.6) pg / ml, respectively, with a statistically significant difference P <0.05.Keywords: Giardia lamblia; Cytokines; Immunoglobulins.